Pembelajaran Berbasis Game: Manfaat, Tantangan, dan Strategi Implementasi dalam Konteks Pendidikan Tinggi Pada Akademi Keuangan Perbankan Nusantara (AKUBANK) - Khairani, Putri; Khadavi, Muammar; Salsyabillah, Miralda (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
The purpose of this study to determine the benefits, challenges and strategies for implementing game-based learning at the Akademi Keuangan Perbankan (AKUBANK). The research method uses a qualitative approach which includes data collection through interviews and observation of AKUBANK lecturers and students. The research participants consisted of lecturers and first semester students of introductory accounting courses. The results of this study indicate that game-based learning has significant benefits in the context of higher education at AKUBANK. The introduction of games into the learning process can increase student motivation and participation, facilitate understanding of academic concepts, encourage creativity and critical thinking, and increase social interaction and cooperation among students. However, this study also identified challenges in implementing game-based learning at AKUBANK, including designing and developing effective game content, the need for adequate technical resources, monitoring student progress, as well as training and support needed to integrate game-based lectures.